Baking Bittersweet: Mothers' Dessert-Making Behind Bars. (December 2019) - Stearns, A. Elizabeth
Food is a significant component of life; its preparation is gendered and associated with caregiving roles. For incarcerated women, food is especially salient. Inmate-created recipes can assist with asserting pro-social identities and responding to powerlessness. It is less certain if incarcerated mothers draw upon recipes to emphasize mothering identities. Therefore, this study uses focus groups at a jail and additionally analyzes contributed recipes to explore the way dessert-making behind bars affirms motherhood. Results suggest that dessert preparation aids in disrupting negative stereotypes, illuminates the fragility of incarcerated mothering, and highlights agentic practices. Implications for policy and research are included.